TEAM TRAINING SIMULATION IN PERIOPERATIVE NURSING EDUCATION - Granger, Jocelyn; Hebb, Trudy; Lavallee, Rolanda; Murray, Michelle (Operating Room Nurses Association of Canada Journal, 2011)
The current traditional apprenticeship model in healthcare is no longer meeting the needs of our learners.1 This model requires learners to master various core skills, carry out a procedure under supervision, and relate simultaneously to other staff in the complex operating room. The approach of “see one, do one, teach one” is considered, by some, to no longer be acceptable. Perioperative nursing educators are, as a result, now faced with the challenge of finding education modalities that will facilitate the learner’s journey to competence and the delivery of safe patient care. The purpose of this paper is to discuss team training simulation in the competence development of perioperative nursing learners at the Registered Nurses Professional Development Centre (RNPDC) in Halifax, Nova Scotia.